Cognitive and Child Language Development and Involvement in Learning - Tirta Rhamadanty (Yayasan Insan Mulia Bima, 2023)
This article examines two important stages in the process of children's learning development, namely cognitive development and linguistic development, which is usually called language. The teacher's capacity to incorporate the qualities and uniqueness of each child into the learning process is essential because each child possesses these qualities in two interdependent growth processes. Appropriate learning strategies and techniques will be provided by teachers who are aware of their students' developmental needs to promote good cognitive and linguistic growth. The aim of this research is to investigate Jean Piaget's theory of cognitive development. This research uses a literature review study method (Library Research). Based on the findings of this study, Jean Piaget offered a new theory that each stage of a child's cognitive development is different and has its own characteristics. Piaget emphasized the importance of actual direct involvement in the subject being studied when learning occurs. Additionally, Piaget urged all educators to help students move through the many phases of cognitive development in an orderly and accurate manner. This article also shows that teachers can act as facilitators and motivators to support the growth of these two aspects of learning.